Bacterial Spectrum of Acute Otitis Media in Bulgarian Children during the 10-Valent Pneumococcal Conjugate Vaccine Era - Setchanova, Lena; Stancheva, Iglika; Popova, Diana; Alexandrova, Alexandra; Mitov, Ivan (Journal of Pediatric Infectious Diseases, 2020)
Objective The 10-valent pneumococcal conjugate vaccine (PCV10) was introduced in Bulgaria for universal childhood vaccination in 2010. The objective of this study was to describe bacterial pathogens responsible for acute otitis media (AOM) in children in the era of routine PCV10 immunization.Materials and Methods Middle ear fluid (MEF)/otorrhea or nasopharyngeal specimens were collected between May 2012 and April 2017 from 425 children aged < 12 years diagnosed with AOM; 71.5% of them were vaccinated. Capsular types of Streptococcus pneumoniae and Haemophilus influenzae and antimicrobial nonsusceptibility were determined.Results Among 240 children with “severe” AOM, the studied specimens were MEF/otorrhea, and a total of 132 (55.0%) children were culture-positive. The most frequently identified bacteria were S. pyоgenes (31.1%), followed by Staphylococcus aureus (21.2%), S. pneumoniae (20.4%), and nontypeable H. influenzae (12.1%). Among 185 nasopharyngeal specimens obtained from children at the onset of a “mild” AOM episode, 67.0% were culture-positive for otopathogens. The most common pathogens were S. pneumoniae (41.9%), followed by H. influenzae (25.8%), Moraxella catarrhalis (23.4%), and S. pyоgenes (14.5%), alone or in combinations. Among children with pneumococcal AOM (79), PCV10 serotypes (VTs) were 21.5%. A high prevalence (50%) of nonvaccine serotypes 3 (14), 19A (11), and 6C (7) was found among vaccinated children. Rates of nonsusceptibility of S. pneumoniae to penicillin, amoxicillin and erythromycin, and of multidrug resistance, were 51.2, 10.1, 51.2, and 51.2, respectively. The rate of ampicillin-non-susceptibility in H. influenzae was 25%. All M. catarrhalis isolates were β-lactamase producers, and 32.2% of S. pyogenes were erythromycin-resistant.Conclusion Following implementation of PCV10, S. pyogenes was the most prevalent pathogen in children with “severe” AOM. Numbers of S. pneumoniae recovered from MEF/otorrhea significantly decreased, as did the overall proportion of VTs among AOM patients. Streptococcus pneumoniae, H. influenzae, and M. catarrhalis were the most commonly found pathogens in the nasopharynx of children with less severe AOM episodes.
Keywords: AOM; otopathogens; MEF; nasopharynx; PCV10